A Review of Current Evidence for TNF Inhibitor Switching in Psoriatic Arthritis. Issue 3 (June 2016) - Abramson, Sarah R.; Khattri, Saakshi; Lebwohl, Mark
TNF inhibitors have been proven to be effective in treating psoriatic arthritis, however not every patient responds to or tolerates treatment. Between 20% and 40% of patients are switched to a different TNF inhibitor, and 5% to 15% are eventually treated with three different TNF inhibitors. Loss of efficacy is the most common reason patients fail TNF inhibitor therapy, followed by adverse effects. Less than a quarter of patients who switched TNF inhibitors did so due to lack of primary response. The majority of data demonstrates that switching can be clinically beneficial after failure of one TNF inhibitor, but is associated with lower response rates compared to initial treatment. Drug survival rates also decrease with multiple courses of treatment. If a psoriatic arthritis patient fails two TNF inhibitors, it may be more efficacious to switch to one of the newer biologics with an alternate mechanism of action.